Antibacterial ability and molecular characterization of probionts isolated from gut microflora of cultured red tilapia - Lim, Char Yee; Md Yasin, Ina Salwany; Abdelhadi, Yasser Mohamed (Academic Journals, 2013)
Four bacterial isolates, which proved to have the potential to be used as probiotics, were used to study their genotypic characterization using analysis of 16S rRNA gene sequence, antagonistic ability and safety when applied on tilapia via immersion. Gram staining showed that all 4 probionts were Gram positive bacteria. Three probionts were rod in shape and the fourth was cocci in shape and arranged in grape-like cluster. These 4 probionts were also identified using 16S rRNA gene sequencing and their identities were Paenibacillus barcinonensis strain D12, Paenibacillus sp. strain D14, Staphylococcus cohnii strain Bll and Bacillus megaterium strain E28, respectively. All of the probionts were examined for their antagonistic ability against pathogenic bacteria (Vibrio alginolyticus ATCC 33839, Aeromonas salmonicida and Aeromonas hydrophila ATCC 35654) under in vitro conditions by using cross-streaking method. P. barcinonensis strain D12 and Paenibacillus sp. strain D14 have shown stronger antagonistic ability than S. cohnii strain Bll and B. megaterium strain E28 in the antagonism test. P. barcinonensis strain D12 and Paenibacillus sp. strain D14 were chosen to test their safety on tilapia due to their better performance in antagonism test. Both probionts, P. barcinonensis strain D12 and Paenibacillus sp. strain D14, were safe for tilapia.